Manajemen Layanan Bimbingan dan Konseling Pribadi-Sosial di Madrasah Aliyah Negeri 3 Palembang - Aina Warda Agissa; Tutut Handayani; Asri Karolina; Nyayu Soraya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Personal-social guidance and counseling services constitute an important component of student developmental support, but their effectiveness depends on the integration of program management functions. This study aims to analyze the management of personal-social guidance and counseling services at MAN 3 Palembang, including planning, organizing, implementation, supervision, and evaluation, while identifying factors that support and hinder program implementation. A descriptive qualitative approach was employed. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing and verification. Data credibility was examined through source and technique triangulation. The findings indicate that guidance and counseling services are supported by planning documents, formal task allocation, diverse service activities, and supervisory mechanisms. However, the connections among management functions have not yet been fully integrated. Program planning responds to students’ needs, but needs assessment and documentation remain insufficiently standardized. Coordination among school leaders, counselors, homeroom teachers, and subject teachers remains largely informal, while the limited number of counselors and some students’ perceptions of counseling services restrict equal access to services. Supervision has been implemented, but program evaluation has not been systematically documented as a basis for subsequent planning. This study formulates a needs-based and continuous-improvement management model linking needs analysis, program planning, actor coordination, service implementation, monitoring and evaluation, and program improvement.